2003
DOI: 10.1002/sia.1512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of target surface degradation on the properties of r.f. magnetron‐sputtered calcium phosphate coatings

Abstract: This paper reports a detailed study of how repeated r.f. magnetron sputtering from a hydroxyapatite (HA) powder target affects the nature and reproducibility of a sequential series of thin-film coatings deposited onto Ti6Al4V substrates. An evaluation of the effective lifespan of the HA sputter targets and the reproducibility of the calcium phosphate (CaP) coatings produced from them has been made from Fourier transform infrared spectroscopy, XPS and, as appropriate, atomic force microscopy and SEM/energy disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 47 publications
16
34
0
Order By: Relevance
“…The P2p spectral envelope could also be fit with two peaks, each of which comprises an unresolved doublet. The most intense of these bands is located at 132.72 eV (1), while the weaker band is centered at 133.99 eV (2), corresponding to P-O and P-O-H bonding in HPO 4 2-, respectively [8]. These data are consistent with the chemical structure of HAp.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The P2p spectral envelope could also be fit with two peaks, each of which comprises an unresolved doublet. The most intense of these bands is located at 132.72 eV (1), while the weaker band is centered at 133.99 eV (2), corresponding to P-O and P-O-H bonding in HPO 4 2-, respectively [8]. These data are consistent with the chemical structure of HAp.…”
Section: Resultssupporting
confidence: 80%
“…4 indicates the presence of two distinct bands. The first of these contributions is located at 530.60 eV (1) and is attributed to O-P bonding and the second, found at 531.62 eV (2), is associated with oxygen bonded to OH -groups [8][9][10]. The P2p spectral envelope could also be fit with two peaks, each of which comprises an unresolved doublet.…”
Section: Resultsmentioning
confidence: 97%
“…All the reflections from the target after sputtering for 630 ks were indexed to -TCP structure. The ICP analysis for ''annular race track'' 45) of the target surface revealed that the composition, Ca/P molar ratio, was almost the same as that before sputtering. Boyd et al 45) applied hydroxyapatite (HAp) targets pressed at 10 MPa for 7.2 ks using a pressure filtration die assembly in RF magnetron sputtering.…”
Section: Methodsmentioning
confidence: 93%
“…The ICP analysis for ''annular race track'' 45) of the target surface revealed that the composition, Ca/P molar ratio, was almost the same as that before sputtering. Boyd et al 45) applied hydroxyapatite (HAp) targets pressed at 10 MPa for 7.2 ks using a pressure filtration die assembly in RF magnetron sputtering. They indicated that the HAp degraded during sputtering with becoming hydroxyl ion deficient forming other calcium phosphate phases and Ca(OH) 2 accompanying an increase in Ca/P ratio.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation